The prevalence of hepatitis A virus and parvovirus B19 in source‐plasma donors and whole blood donors in China. Issue 6 (13th November 2015) - Han, T.; Li, C.; Zhang, Y.; Wang, Y.; Wu, B.; Ke, L; Liu, G; Li, L.; Liu, Y.; Liu, Z.
SUMMARY: Aims: To compare the prevalence of hepatitis A virus (HAV) and human parvovirus B19 (B19V) between source‐plasma (SP) donors and whole blood (WB) donors. Background: In China, source plasma is in severe shortage while plasma recovered from WB is in surplus. Thus, the government is considering transferring the recovered plasma (RP) to produce plasma derivatives. HAV and B19V are two pathogens threatening the safety of plasma‐based derivatives. However, there is no data about if transferring of the RP to produce plasma derivatives will increase the risk of HAV and B19V infection. Thus, we compared the prevalence of HAV and B19V between SP donors and WB donors in this study. Methods: A total of 5030 samples from SP donors and 5040 samples from WB donors were collected. All the samples were tested for HAV RNA and B19V DNA and tested for HAV IgM by enzyme‐linked immunosorbent assay (ELISA). Results: The prevalence of B19V DNA was 0·06% (95% confidence interval (CI), 0–0·09%) in WB donors and 0·079% (95%CI, 0–0·12%) in SP donors, respectively. No significant difference was found in the prevalence of B19V DNA between SP donors and WB donors. The prevalence of anti‐HAV IgM in SP donors was 0·079% whereas no WB donor sample was found anti‐HAV IgM reactive. Conclusions: The transfer of RP to producing plasma derivatives will not increase the risk of transmission of HAV and B19 through plasma products.